AKTIVITAS FISIK DAN SCREEN TIME REMAJA DI KOTA SURABAYA PADA MASA PANDEMI COVID-19 - Nissa, Febby Alfu Khoirun; Mustar, Yetty Septiani; Kumaat, Noortje Anita; Susanto, Indra Himawan; Hariyanto, Agus (Jurnal Sporta Saintika, 2021)
COVID-19 has changed many patterns of human life in various parts of the world, including social restrictions that have implications for the closure of schools and sports facilities. This study aims to identify physical activity and screen time among adolescents in Surabaya during the COVID-19 pandemic. A quantitative descriptive design using a survey method was used in this study. The research sample consisted of 246 teenagers in the city of Surabaya using a purposive random sampling technique. The data collection technique was carried out using an online questionnaire. This study revealed decreased physical activity and increased screen time, which is dominated by young women in Surabaya during the COVID-19 pandemic. It is needed the role of various parties from the government, health agencies, and parents to promote and help children to stay active and balance physical activity as well as the use of daily screen time in maintaining fitness, increasing body immunity and work productivity, preventing obesity and cardiovascular disease during COVID-19 pandemic.